2018
DOI: 10.24171/j.phrp.2018.9.5.02
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Virulence Factors and Antimicrobial Resistance among <italic>Escherichia coli</italic> Isolated from Urinary Tract Infections and Commensal Isolates in Tehran, Iran

Abstract: ObjectivesUropathogenic Escherichia coli (UPEC) are the major cause of urinary tract infections (UTIs). Here, we determined whether sensitivity to antibiotics was related to the prevalence of iron scavenging genes, or to biofilm and hemolysis formation.MethodsA total of 110 UPEC and 30 E coli isolates were collected from the urine of UTI patients and feces of healthy individuals without UTI, respectively. The presence of iron receptor genes and phenotypic properties were evaluated by polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
15
35
0
Order By: Relevance
“…In the present study, biofilm formation was evident in majority of UPEC; this is in agreement with study done by Karam et al [15], Sharma et al [19] and Dumaru et al [20]. Study done by Fattahi et al [21] have observed a higher rate of biofilm formation (90%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, biofilm formation was evident in majority of UPEC; this is in agreement with study done by Karam et al [15], Sharma et al [19] and Dumaru et al [20]. Study done by Fattahi et al [21] have observed a higher rate of biofilm formation (90%).…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed greater production of hemolysin by UPEC (32.3%, n = 34) than the control strains (11.4%, n = 12), which is statistically significant (P < 0.0001). This finding is consistent with several studies done previously [13, 15, 16]. A similar study done by Mittal et al [9] revealed a higher rate of hemolysin production(47%) in UPEC, while Kauser et al [17] observed only 21% were hemolysin producer.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have determined that hemolysin-producing E. coli isolates were less resistant to tetracycline, nalidixic acid, cefotaxime and cotrimoxazol than non-hemolytic isolates [ 26 , 27 ]. In addition, there is a significant correlation between resistance to ceftazidime and cefotaxime with the presence of fyuA and iutA iron genes in UPEC isolates, while isolates harbouring the chuA genes were more susceptible to sulfamethoxazole [ 27 ].…”
Section: Relationship Between Antibiotic Resistance and Virulencementioning
confidence: 99%
“…These antimicrobial resistance patterns tend to differ from one geographical region to another (13). Timely and appropriate treatment is crucial in the management of UTIs; however, this should be based on evidence from regional antimicrobial susceptibility results, knowledge of the virulence genes and bio lm formation (14) (15). Understanding the link between bio lm formation, presence of virulence genes and antimicrobial resistance distribution in UPEC strains is key in designing effective strategies and measures for prevention and management of UTIs especially severe, recurrent and complicated UTIs (14).…”
Section: Introductionmentioning
confidence: 99%